A chaotic agriculture/agri-industry ratio growth model - Jablanović, Vesna (Economics of Agriculture, 2010)
Chaos theory , as a set of ideas , attempts to reveal structure in aperiodic, unpredictable dynamic systems. Chaos embodies three important principles: (i) extreme sensitivity to initial conditions; (ii) cause and effect are not proportional; and (iii) nonlinearity. The basic aim of this paper is to provide a relatively simple the agriculture/ agri-industry ratio growth model that is capable of generating stable equilibria, cycles, or chaos depending on parameter values. A key hypothesis of this work is based on the idea that the coefficient π = γ +1 plays a crucial role in explaining local stability of the agriculture/agroindustry ratio, where γ is a suitable parameter.